The didactic adaptation of linguistic classifications of legal language synonyms as a preparatory stage for teaching synonyms in a legal English course - K. G. Chiknaverova (Вестник Северо-Кавказского федерального университета, 2025)
Introduction. The author examines the feasibility and possibilities of adapting linguistic research data on synonyms typical of legal English texts for teaching purposes. It identifies the most frequent features of pairs of synonyms in commercial legal documents, based on that, a classification is proposed that takes into account the perception of the synonyms by Russian-speaking law students.Goal. The purpose of the article is to justify the need to adapt linguistic data as a stage preceding the preparation and creation of teaching materials for a Legal English course. The category of students such course is designed for does not possess deep linguistic knowledge, yet they need to understand all the nuances of term usage and other high-frequency vocabulary, which is one of the key requirements for lawyers.Materials and methods. The methodological foundation of the research includes the method of continuous sampling, comparative analysis, frequency analysis, cluster analysis, classification, and typology. The study applies the principle of adaptation of linguistic research. It presents a comparative analysis of Russian and foreign classifications of synonyms for legal terms.Results and discussion. Interchangeable synonyms consist of cognate and non-cognate words that show no variation in meaning within the studied contexts; syntactic expressions with minor changes in terminological phrases; propositional structures that can be paraphrased; simple forms that serve as equivalents to compound ones; and Anglo-American correspondences. The second group involves stylistically conditioned expressions. The third comprises forms distinguished by a single semantic feature, regardless of context. The fourth category refers to elements differing by one or several features, depending on context or compatibility. False synonyms are also part of this classification.Conclusion. The identified classifications of synonyms are based on different features: parts of speech, the degree of overlap of semantic fields, syntactic functions, as well as structural, orthographic, and morphological characteristics. The classification adapted for teaching purposes focuses on identifying interchangeable and non-interchangeable lexical elements.